Penerapan Pelayanan Publik Yang Berinovasi dalam mewujudkan Good Governance Pada Sektor Publik - Anjas Muharman; Aldri Frinaldi (UIR Press, 2023)
Public service has not worked well as a tool to coordinate the responsibilities of the government and the people. This is indicated by the fact that there are still overlapping policies and the lack of competence of public officials and the tendency to innovate is a phenomenon where many policies have been canceled or changed by the government. Therefore, new policy innovations are needed that can significantly support efforts to address community problems. To achieve good governance, this study aims to describe and analyze how service innovation works from the perspective of a public administration approach. This study is based on literature research and will later collect information on implementing service innovation for service providers, cultivating a culture of innovation in the public sector, and how innovation can improve organizational performance in achieving bureaucratic change. The results of this study are the application of an innovative culture, the urgency of public service innovation in improving organizational performance, and the urgency of implementing innovation for the public sector in achieving transformation.